Cavity ring-down spectrometer for high-fidelity molecular absorption measurements. (August 2015) - Lin, H.; Reed, Z.D.; Sironneau, V.T.; Hodges, J.T.
Abstract: We present a cavity ring-down spectrometer which was developed for near-infrared measurements of laser absorption by atmospheric greenhouse gases. This system has several important attributes that make it possible to conduct broad spectral surveys and to determine line-by-line parameters with wide dynamic range, and high spectral resolution, sensitivity and accuracy. We demonstrate a noise-equivalent absorption coefficient of 4×10 −12  cm −1  Hz −1/2 and a signal-to-noise ratio of 1.5×10 6 :1 in an absorption spectrum of carbon monoxide. We also present high-resolution measurements of trace methane in air spanning more than 1.2 THz and having a frequency axing with an uncertainty less than 100 kHz. Finally, we discuss how this system enables stringent tests of advanced line shape models. To illustrate, we measured an air-broadened carbon dioxide transition over a wide pressure range and analyzed these data with a multi-spectrum fit of the partially correlated, quadratic speed-dependent Nelkin–Ghatak profile. We obtained a quality-of-fit parameter in the multispectrum fit equal to 36, 000, thus quantifying small-but-measurable limitations of the model profile. This analysis showed that the line shape depends upon collisional narrowing, speed dependent effects and partial correlations between velocity- and phase-changing collisions. Abstract : Highlights: We present a near-infrared cavity ring-down system for measurements of greenhouse gases. We show a CO spectrum with a signal-to-noise ratio of 1.5 million. We show CO2 line shape measurements with quality of fits greater than 35, 000:1. We show a noise equivalent absorption coefficient of 4 × 10 − 12 cm − 1 / Hz 1 / 2 . We achieve an uncertainty of the frequency axis of 100 kHz over 1.2 THz range.